New Public Management : Perkembangan dan Aplikasi dalam Mereformasi Organisasi Publik - Subhan Subhan; Agus Rianto (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2023)
At the conceptual level, New Public Management (NPM) is an effort to respond to the challenges of changes in the environment of public organizations as a result of dramatic changes in the external environment both due to globalization, democratization, scientific advances and the increasing demands of society on government. Therefore, public organizations must be adaptive to the changes that occur, this effort is carried out by reforming themselves by adopting the private sector in carrying out their management. The adoption of private sector management in the public sector is known as the New Public Management (NPM) concept. NPM has been implemented in various countries and is the leading and dominant model in carrying out reforms in the public sector